Detection of occult hepatitis B in serum and oral fluid samples - Moyra Machado Portilho; Leticia Cancella Nabuco; Cristiane Alves Villela-Nogueira; Carlos Eduardo Brandão-Mello; José Henrique Pilotto; Geane Lopes Flores; Lia Laura Lewis-Ximenez; Elisabeth Lampe; Livia Melo Villar (Memorias do Instituto Oswaldo Cruz)
In occult hepatitis B infection (OBI), hepatitis B virus DNA (HBV DNA) can be detected in serum samples; however, oral fluid collection for detection of HBV DNA has not yet been explored, despite the availability of collection devices. Serum and oral fluid samples from 45 hepatitis B core antibody (anti-HBc)-positive patients were collected for the amplification of the HBV polymerase gene. HBV DNA was detected in five serum and four oral fluid samples (the detection limit for oral fluid was 1.656 log IU/mL in paired serum). In conclusion, simple methodologies of sample collection and in-house polymerase chain reaction (PCR) allowed detection of HBV DNA, and these could be used to improve the diagnosis of OBI, especially in locations with limited resources.